Analysis of the Relationship between Energy Consumption, Foreign Direct Investment, and Labor Force Participation by Vector Error Correction Model: The Case of Kazakhstan - Aidarova, Aina B.; Zhadigerova, Gulshat Abdimutalipovna; Abilkassym, Ainur; Baibulekova, Lyailya Abdybayevna; Balabekova, Dina B.; Ilasheva, Saule A. (International journal of energy economics and policy, 2023)
This study examines the relationship between energy consumption, foreign direct investment, and labor force participation rate in Kazakhstan for the 1991-2021 period. Data on energy consumption are retrieved from the enerdata website, and data on foreign direct investment and labor force participation rate from the World Bank website. The Vector Error Correction Model (VCEM) method was used for data analysis. Research findings have shown that foreign direct investments have an effect on energy consumption for Kazakhstan both in the long run and the short run. The study found that although the labor force participation rate has an effect on energy consumption in the short term, it has no effect in the long term. These results are also important in terms of indirectly showing the long-term effects of foreign direct investments on the economy. The study used annual series for all three variables. Another important subject of study for explaining this relationship may be the use of series in different periods (especially quarterly).